Effect Of Bank And Macro Economic Performance On Bank Capital Supporters In Indonesia - Putra Indra; Abraham Prima; Farah Margaretha Leon (Universitas Trisakti, 2019)
This study was conducted to examine the effect of bank performance and macroeconomics on capital buffer in banks listed on the Indonesia stock exchange in the 2014-2018 period. There are 26 banks that become the sample of this study after purposive sampling. The capital buffer used is the difference between the Capital Adequate Ratio and the minimum capital determined by the regulator. While the independent variables used consist of bank performance, namely Return on Equity, Bank Size, Liquidity, Non-Performing Loans, Net Profit, Loan Growth and Total Loans over Total Assets. Macroeconomic variables also become a factor that is analyzed on the effect of bank capital buffer. By using the Generalized Method of Moment (GMM) regression model, it can be seen that the bank's performance variables measured through Return on Equity, Liquidity, Net Profit and Total Loan over Total Assets have a significant effect on banking capital buffer in Indonesia. Whereas macroeconomic variables measured through GDP do not have a significant effect on banking capital buffer in Indonesia.